Answer:
V=20
Step-by-step explanation:
Simplify both sides of the equation.
4−2(v+9)=26
4+(−2)(v)+(−2)(9)=26(Distribute)
4+−2v+−18=26
(−2v)+(4+−18)=26(Combine Like Terms)
−2v+−14=26
−2v−14=26
Step 2: Add 14 to both sides.
−2v−14+14=26+14
−2v=40
Step 3: Divide both sides by -2.
−2v
−2
=
40
−2
v=−20
Answer:
x=-1
y=4
z=7
Step-by-step explanation:
3x + y - z= -6(1)
2x - y + 2z = 8(2)
4x + y - 3z = -21(3)
(1)+(2): 5x+z=2(4)
(2)+(3): 6x-z=-13(5)
(4)+(5): 11x=-11
x=-1
so z=2-5x=7
y=-6-3x+z=4
When drawn out, the answer becomes the sum of the bases of two triangles
Answer: 70 m
Step-by-step explanation:
3, -12,7should be the correct answers
Answer:
$1.50 bro
Step-by-step explanation: